Ideologising Europe and europeanising ideology: Political party ideologies and the European Union - Marta Lorimer (London School of Economics and Political Science (LSE), European Institute, 2024)
There is a persistent narrative in European Union politics that presents the EU as 'nonideological'. A closer look, however, reveals that EU integration has been (and still is) the source of multiple ideological struggles, especially for political parties. However, we still know little about how parties interpret European integration through ideological lenses and how this in turn affects (if at all) their existing ideological commitments. This paper sets itself the task of conceptualising the relationship between political party ideology and the process of European integration. It argues that there are two ways to study this relationship. The first is to focus on the 'ideologisation' of Europe and bring attention to how parties interpret European integration in light of their existing beliefs. The second approach looks at how these adaptations affect parties' existing commitments, leading to a 'Europeanisation' of ideology. Both processes generate tensions parties must navigate and opportunities they can take advantage of.
Keywords: 330; Ideologie; Europäische Integration; EU-Staaten